Low temperature preparation of oxygen-deficient tin dioxide nanocrystals and a role of oxygen vacancy in photocatalytic activity improvement - Supanan Anuchai (2018)
© 2017 Elsevier Inc. The introduction of oxygen vacancies (V os ) into tin dioxide crystal structure has been found as an effective method to improve its photocatalytic performance. Herein, oxygen-deficient tin dioxide (SnO 2−x ) nanocrystals were successfully prepared via a facile, one-step hydrothermal method at the temperature lower than those reported previously. The effect of hydrothermal temperature on phase composition and V os content was also firstly investigated. Due to its high oxygen vacancy concentration, the SnO 2−x prepared at 80 °C provides the best photocatalytic degradation of methyl orange under UV–visible light. Scavenger trapping and nitroblue tetrazolium experiments also show that the V os act as electron trapped sites and molecular oxygen adsorption sites, therefore increasing the production of active [rad] O 2 − radical which is the main species governing the photocatalytic activity of SnO 2−x nanocrystals. Raman spectroscopy, X-ray photoelectron spectroscopy, photoluminescence measurement and electron spin resonance investigation clearly indicate that increasing the hydrothermal temperature results in the coexistence of SnO 2−x and Sn 3 O 4 phases and the reduction of V os concentration which are detrimental to the photocatalytic performance. Density functional theory calculations also reveal that the presence of V os is responsible for the upshift of valence band maximum and an extended conduction band minimum, hence a valence band width broadening and band gap narrowing which consequently enhance the photocatalytic performance of the oxygen-deficient SnO 2−x .